The Effect Of Zig-Zag Run And Shuttle Run Exercises On Dribbling Skills In Futsal Games At Senior High School 3 Palopo - Supriadi, Supriadi; Kahar, Irsan; Syahrir, Syahrir; Tunru, Andi Alif (Department of Physical Education, Sport, Health and Recreation, 2023)
The purpose of this study is to examine the effect of Zig-Zag Run and Shuttle Run exercises on dribbling skills in the futsal game at senior high school 3 Palopo. Experimental research is a research conducted to ensure a causal relationship between variables. This research approach is a type of quantitative research that uses secondary data. The population in this study is all futsal athletes at senior high school 3 palopo. The sample is the extracurricular futsal of senior high school 3 palopo as the object studied. The sampling technique used random sampling, which was carried out randomly, Thus the sample in this study is the extracurricular futsal of senior high school 3 palopo totalling 16 students. The sample was divided into two groups by ordinary matched pairing so that the sample is homogeneous. Data processing uses SPSS Version 21 software, multiple linear regression models were used to analyze the data. (1) Zig-Zag Run practice has an effect on dribbling skills in futsal games; (2) Shuttle Run affects dribbling skills in futsal games The results of the study also concluded that both zig-zag and shuttle run exercises were significantly different. The zig-zag exercise is more effective in increasing agility than the shuttle run exercise